JAKE® Multimodal Data Capture System: Insights from an Observational Study of Autism Spectrum Disorder - Ness, Seth L.; Manyakov, Nikolay V.; Bangerter, Abigail; Lewin, David; Jagannatha, Shyla; Boice, Matthew; Skalkin, Andrew; Dawson, Geraldine; Janvier, Yvette M.; Goodwin, Matthew S.; Hendren, Robert; Leventhal, Bennett; et al. (Frontiers in Neuroscience, 2017)
Objective: To test usability and optimize the Janssen Autism Knowledge Engine (JAKE®) system’s components, biosensors, and procedures used for objective measurement of core and associated symptoms of autism spectrum disorder (ASD) in clinical trials. Methods: A prospective, observational study of 29 children and adolescents with ASD using the JAKE system was conducted at three sites in the United States. This study was designed to establish the feasibility of the JAKE system and to learn practical aspects of its implementation. In addition to information collected by web and mobile components, wearable biosensor data were collected both continuously in natural settings and periodically during a battery of experimental tasks administered in laboratory settings. This study is registered at clinicaltrials.gov, NCT02299700. Results: Feedback collected throughout the study allowed future refinements to be planned for all components of the system. The Autism Behavior Inventory (ABI), a parent-reported measure of ASD core and associated symptoms, performed well. Among biosensors studied, the eye-tracker, sleep monitor, and electrocardiogram were shown to capture high quality data, whereas wireless electroencephalography was difficult to use due to its form factor. On an exit survey, the majority of parents rated their overall reaction to JAKE as positive/very positive. No significant device-related events were reported in the study. Conclusion: The results of this study, with the described changes, demonstrate that the JAKE system is a viable, useful, and safe platform for use in clinical trials of ASD, justifying larger validation and deployment studies of the optimized system.